Al-Maujah al-Islāmiyyah al-Ukhrā: Al-Istisyrāq wa al-Dirāsāt al-Islāmiyyah al-Mu‘āṣirah - Abdullah, Muhammad Amin (Al-Jami'ah: Journal of Islamic Studies, 2007)
This article explores the mapping of the development of Islamic studies from its inception to the present, which consists of three waves. The first wave was the study of Islam by internal Muslims themselves. This period lacks comprehensive factors to categorize as an academic study. The second wave was Islamic studies carried out by experts from outside Islam who were called orientalists. This wave of Islamic study involves academically sufficient methodology. Meanwhile, the third wave is generally carried out by internal groups of Muslims who are enlightened and equipped with contemporary sciences, especially humanities.[Tulisan ini berisi pemetaan perkembangan studi Islam dari awal pertumbuhannya hingga masa sekarang, yang dapat dipilah menjadi tiga gelombang. Gelombang pertama dibangun sendiri oleh internal umat Islam. Periode ini tidak memiliki faktor-faktor yang komprehensif untuk sebuah studi akademis. Gelombang kedua merupakan studi Islam yang dilakukan oleh ahli dari luar Islam yang mendapat sebutan sebagai orientalis. Gelombang ini dipandang sebagai studi Islam yang melibatkan metodologi yang cukup sebagai kajian akademik. Sedangkan gelombang ketiga adalah yang umumnya dilakukan oleh kelompok internal Muslim yang tercerahkan dan terbekali dengan keilmuan kontemporer, khususnya ilmu humaniora.]